Reality checks in Mozambique. 2nd Annual Report - Governance - Tvedten, Inge (ORGUT Consulting AB, 2012)
The Reality Checks are implemented between 2011- 2016, with fieldwork being carried out each year in the Districts of Cuamba, Majune and Lago in the Niassa Province. Sub-Team Leaders are Carmeliza Rosário, Minna Tuominen and Inge Tvedten. This is the Annual Report for the 2nd Reality Check, synthesising the main findings from the three sub- reports. The report is written by the Team Leader for the Reality Checks in Mozambique Dr. Inge Tvedten - with support from Carmeliza Rosário, Minna Tuominen and Aslak Orre (Thematic Advisor).
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; gender / género; governance / governação; poverty / pobreza

The Human Rights Impacts of Tree Plantations in Niassa Province, Mozambique - Seufert, Philip; Santos, Ricardo (FIAN International, 2012)
This study investigates the impairing of the rights of peasant communities through the establishment of tree plantations in Niassa province, Mozambique. More particularly, it looks at the impacts of the operations of Chikweti Forests of Niassa on the local population in the districts of Lago, Lichinga and Sanga. In order to do so, it presents an introductory chapter on the general context of Mozambique and the legal framework. This legal framework will serve as a basis on the analysis of the findings of this study using a human rights approach. It contains an overview of national and international provisions relevant to the case. This includes Mozambican national legislation and policies, as well as standards under international human rights law. Regarding the latter, it puts a particular focus on extraterritorial obligations (ETOs), recently clarified by the Maastricht Principles on Extraterritorial Obligations, and includes provisions related to access to land and related resources, as contained in the Voluntary Guidelines on the Responsible Governance of Tenure of Land, Fisheries and Forests.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; rural development / desenvolvimento rural

Nacala Transport Corridor Phase III: Executive Summary Environmental and Social Impact Assessment - Ali, Aymen A Osman (African Development Bank, 2012)
The Government of Mozambique (GoM), acting through the national roads administration (ANE) has made requests to international financial institutions including the African Development Bank, for the improvement of transport infrastructure and for strengthening the institutional capacity of the roads sector. ANE plans to apply a portion of these funds to the environmental and social impact assessment (ESIA) of the project for the rehabilitation of the N13, Cumanba-Mandimba-Lichinga (302 km). The road passes through many small towns and villages and is divided into three sections namely, Cuamba-Mandimba: 148 km (flat terrain), Mandimba-Lichinga148 km: (winding terrain, with some mountainous areas reaching about 1,400m in Lichinga) and MandimbaMalawi Border: 6 km (winding terrain). The N13 is part of two corridors: Nacala –N13/N1and Lichinga – N14/N1 providing a strategic link with the border of Malawi in Mandimba, the ports of Nacala and Pemba in the provinces of Nampula and Cabo Delgado respectively. The road also has the potential to contribute towards poverty reduction and stimulate the development of the country. The road is in fair conditions during the dry season but deteriorates during the rainy season due to poor drainage system and soil erosion. The width of the road varies between 5 and more than 10m and is usually lower than the surrounding terrain.
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; GP - Nampula; L - english / inglês; development partners / parceiros de cooperação; infrastructure / infrastrutura; urbanization / urbanização

Effects of food price shocks on child malnutrition: the Mozambican experience 2008/09 - Arndt, Channing; Hussain, M. Azhar; Østerdal, Lars Peter (World Institute for Development Economics Research (WIDER), 2012)
A propitiously timed household survey carried out in Mozambique over the period 2008-09 permits us to evaluate the short-to-medium run relationship between sudden shocks to food prices and child nutrition status. We link local price inflation with child malnutrition status. We find that the prevalence of underweight amongst children rises in response to a higher inflation rate for basic food products. Stunting and wasting malnutrition measures are mostly insensitive to the inflation rate. The very high food inflation during 2008/09 was responsible for an extra 39,000 moderately underweight and 24,000 severely underweight children.
Keywords: G - Mozambique / Moçambique; L - english / inglês; health / saúde

Afrobarometer Round 5. Summary of Results for Mozambique, 2012 - Centro de Pesquisas de Governação e Desenvolvimento (CPGD) (Centro de Pesquisas de Governação e Desenvolvimento (CPGD), 2012)
The Afrobarometer is a comparative series of public attitude surveys that will be covering up to 35 African countries in Round 5 (2011-2013). Based on representative national samples, the surveys assess citizen attitudes to democracy and governance, markets, and civil society, among other topics. The first round of surveys was conducted between 1999-2001 and covered seven Southern African countries (Botswana, Lesotho, Malawi, Namibia, South Africa, Zambia and Zimbabwe), three countries in West Africa (Ghana, Nigeria and Mali) and two in East Africa (Uganda and Tanzania). Round 2 surveys were completed by November 2003 with four new countries added: Kenya, Senegal, Cape Verde and Mozambique. Round 3 surveys were conducted from March 2005 to February 2006 in the same countries, plus Benin and Madagascar. The 4th Round of surveys covered 20 countries between 2008 and 2009, with the addition of Burkina Faso and Liberia.
Keywords: G - Mozambique / Moçambique; L - english / inglês; M - survey / inquérito; civil society / sociedade civil; governance / governação

Mozambique Social Protection Assessment - Review of Social Assistance Programs and Social Protection Expenditures - Marques, José Silvério (World Bank, 2012)
This assessment shows that Mozambique social protection system is developing. While programs to address most of the risks identified exist, there are still major gaps. Poor families with children are not adequately supported, there is no significant youth program, and subsistence farmers and other workers are not properly protected against recurrent shocks. The government spends a considerable amount of its resources on social protection but most are absorbed by untargeted subsidies and pensions that benefit only a few. This assessment suggests that it will be necessary to address three mutually complimentary issues: developing effective mechanisms to maximize the impact of social protection on reducing poverty; rationalizing public expenditures while filling existing program gaps; and strengthening institutional arrangements. In order to address the multiple challenges Mozambique faces to support particularly vulnerable groups and reduce extreme poverty and food insecurity, the report proposes a gradual approach framed in the existing social protection strategy approved by the Government in 2010.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; social protection / proteção social

Transforming Cash Transfers: Beneficiary and community perspectives of the Basic Social Subsidy Programme in Mozambique - Selvester, Kerry; Fidalgo, Lourdes; Tambo, Neila (Overseas Development Institute (ODI), 2012)
The increasing recognition that social protection programmes in developing countries can play an important role in inclusive and transformative development is welcomed by analysts as a step towards supporting extremely poor households in these countries. In Mozambique, the national cash transfer programme, the Basic Social Subsidy Programme (Programa de Subsídio Social Básico or PSSB), which began in 1992, provides a relatively low value of 130 MTn (approx. $4.5) to 380 MTn (approx. $13), narrowly targeted transfer to nearly 300,000 extremely vulnerable households. The programme has clear political commitment to sustainability, using state funds. The PSSB is not an isolated intervention; rather, it is part of a broader social protection platform that includes providing support to households that temporarily find themselves unable to overcome a specific shock or event, along with social assistance delivered through the health and education sectors. The social protection system in Mozambique is in the process of being reformed and modernised, which should result in a more transparent and accountable system. One of the key reforms involves the development of a management information system (MIS) that will provide an integrated technical platform for the management of the social assistance programmes. The key research objectives of this study are:  to explore the views, experiences and perceptions of cash transfer programme beneficiaries and other community members (non-beneficiaries) in order to ensure that they are better reflected in policy and programming  to gather perceptions and experiences from programme implementers  to provide examples of best practice on how to involve beneficiaries and communities in participatory monitoring and evaluation (M&E) of cash transfer programmes  to build the capacity of national researchers in qualitative and participatory data collection and analysis. The research report presents background information on cash transfers in Mozambique in order to frame the detailed qualitative and participative study conducted in two districts in the southern province of Gaza, Chokwe and Chibuto. The research focuses on people with disabilities who receive the cash transfer. Currently, of the 286,176 people with disabilities living in poverty), less than 14,000 households with disabled members are receiving the government cash transfer. The fieldwork for the research was preceded by a demand generation consultation (DGC) exercise that provided valuable insights into stakeholders’ concerns in terms of the delivery and impact of the PSSB on beneficiaries’ lives, particularly on households headed by people with disabilities. Stakeholders were concerned that the research examined the extent to which beneficiaries are aware of their rights, the procedures and regulations of the PSSB, and whether there was any transparency, at local level, in the selection of beneficiaries. The research team used a wide variety of qualitative data collection tools with a view to collecting in-depth information about the impact of the cash transfer on beneficiaries’ lives and perceptions of all stakeholders (including beneficiaries) about the extent to which the PSSB was a transparent and accountable mechanism. All of the fieldwork tools were pre-tested in the peri-urban area of BairroAreoporto, Maputo city. There was unanimous agreement among all stakeholders interviewed that the value of the transfer was too low to be considered a transformative measure and is rather perceived as a minimum welfare payment to reduce the possibility of vulnerable households becoming destitute. Advocacy is needed to increase the real value of the transfer in order to strengthen resilience of the most vulnerable households. The Mozambique Government’s implementing agency, the National Institute for Social Action (INAS), recognises that the fiscal space for the programme is still relatively constrained, whic vi means there is a lack of sustainable financial capacity to address the problems of all vulnerable groups that fall within its mandate. Improving beneficiary management and outsourcing payments to private sector providers are the main pillars of change currently proposed by INAS to begin to address this issue. Our research highlighted the need for coordinated and harmonised support to the sector by development cooperation partners to ensure that reform efforts build an integrated social protection system rather than creating unsustainable ad hoc programmes that satisfy the short-term goals of individual donor agencies. The research clearly identified how little information was available about the PSSB at all levels of the system, leading to a lack of transparency, and ultimately a lack of accountability to beneficiaries. The report recommends that there is a need for a comprehensive communication and education strategy to reach all the stakeholders, including the use of media (particularly radio), capacity-building and refresher training for staff and community liaison agents, and the production and dissemination of simple printed materials describing key elements of the programme. There was a clear indication in the research that people with disabilities are under-represented in the programme, and more importantly do not feel that they have a right to complain about any aspects of it. A lack of understanding (on the part of the implementing agency and staff) about the needs of the programme’s target groups has led to people feeling that the cash transfer was solely a pension provided to older people, those who are unable to work and those who are chronically poor. Physical access to the people who fill in the application forms1 was considered less of a barrier than feelings of lack of entitlement by extremely poor people living with a disability. Making targeting mechanisms and criteria more transparent (easily understood) through clear and well-disseminated information would reduce the bias against applicants with disabilities. Our research also found that demand for accountability from beneficiaries was low, as they generally have few expectations of the government institutions or other agencies that provide assistance ‘system’; creating a demand for transparency is a challenge that will require considerable political will, information campaigns and engagement of multiple stakeholders. With the aforementioned modernisation of the social protection system, there are openings to improve transparency that could lead to greater accountability at all levels. These include the development of an effective grievance system to increase and improve communication between beneficiaries and INAS, which, over time, could create a sense of mutual accountability and trust. In addition, there were calls from INAS officials, local leaders and beneficiaries for independent, participatory monitoring of the programme. The recently formed Civil Society Platform for Social Protection is designing a community-based monitoring system for social assistance programmes, which will be piloted in 2013. Government actors as well as non-government actors in Mozambique recognise that there is a lack of structured and institutionalised coordination and collaboration between entities working in the social protection sector. This leads to duplication of efforts in some areas and glaring service gaps in others. Mechanisms need to be set up at local level to bring these entities together to share information and establish simple working guidelines for collaboration. Each district should establish locally specific mechanisms based on guiding principles of openness, collaboration and transparency of action. There are deep concerns about the human resource capacity of INAS to fulfil its wide mandate of not only providing social assistance transfers but moving towards case management of beneficiaries and the delivery of a transparent and accountable social protection system. Throughout the report, the voice of programme beneficiaries is clearly presented, indicating above all the urgency required to deliver more effective and efficient social protection programmes that will give the most disenfranchised people an opportunity to participate socially and economically in society.
Keywords: *tagged; Ethnographic Studies; G - Mozambique / Moçambique; L - english / inglês; government policy / politica governamental; social protection / proteção social

Citizen voice and state accountability: towards theories of change that embrace contextual dynamics - Tembo, Fletcher (Overseas Development Institute, 2012)
The development industry is increasingly pushing practitioners to achieve results, and to do better in demonstrating what works, what does not, and explaining why. There is a growing interest in going beyond the measurement of results to being able to understand the basis for success or failure. Consequently, the development of explicit theories of change (ToCs) is starting to be viewed as central to this process, as a key part of what constitutes ‘rigour’ in impact evaluations. Citizen voice and accountability (CV&A) project interventions produce and reproduce diverse outcomes that are not amenable to linear models of ToCs. This paper uses a critical analysis of CV&A cases from the Mwananchi Governance and Transparency Fund (GTF) programme to examine how citizen voice and accountability happens in different governance contexts. The analytical framework used in this paper draws on the well-known tools of outcome mapping (OM) and political economy analysis (PEA). Key points: Enabling citizens to influence government accountability is a complex process involving political dynamics at the citizens’ interface with state institutions; Developing explicit theories of change (ToCs) from the start of programme planning helps planners delve into complex citizen–state dynamics; and Fusing political economy analysis and outcome mapping tools can help develop a deeper understanding of these dynamics to generate more effective ways to achieve outcomes.
Keywords: #Reviews & Framing / Revisões e Organização; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); accountability / responsabilização; civil society / sociedade civil

Reality checks in Mozambique: building better understanding of the dynamics of poverty and well-being. Annual Report, Year One - Tvedten, Inge (ORGUT Consulting AB, 2012)
he Reality Checks are implemented 2011-2016 and each year field work is carried out in the Municipality of Cuamba, the District of Lago and the District of Majune in the Niassa Province. This is the Annual Report for Year One of the Reality Checks and aims at summarising the conclusions based on the findings from the field sub-report from each study location.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Cuamba; GD - Lago; GD - Majune; GP - Niassa; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; gender / género; poverty / pobreza